Reduced-order anti-synchronization of the projections of the fractional order hyperchaotic and chaotic systems - Srivastava, Mayank; Agrawal, Saurabh K.; Das, Subir (Walter de Gruyter, 2013)
The article aims to study the reduced-order anti-synchronization between projections of fractional order hyperchaotic and chaotic systems using active control method. The technique is successfully applied for the pair of systems viz., fractional order hyperchaotic Lorenz system and fractional order chaotic Genesio-Tesi system. The sufficient conditions for achieving anti-synchronization between these two systems are derived via the Laplace transformation theory. The fractional derivative is described in Caputo sense. Applying the fractional calculus theory and computer simulation technique, it is found that hyperchaos and chaos exists in the fractional order Lorenz system and fractional order Genesio-Tesi system with order less than 4 and 3 respectively. The lowest fractional orders of hyperchaotic Lorenz system and chaotic Genesio-Tesi system are 3.92 and 2.79 respectively. Numerical simulation results which are carried out using Adams-Bashforth-Moulton method, shows that the method is reliable and effective for reduced order anti-synchronization.
Keywords: anti-synchronization; chaotic Genesio-Tesi system; fractional order derivative; hyperchaotic Lorenz system; Laplace transforms method; reduced order